H-GA-PSO Method for Tuning of a PID Controller for a Buck-Boost Converter Modeled with a New Method of Signal Flow Graph Technique - Leila Mohammadian; Ebrahim Babaei; Mohammad Bagher Bannae Sharifian (Bulletin of Electrical Engineering and Informatics, 2015)
In this paper, a new method of signal flow graph technique and Mason’s gain formula are applied for extracting the model and transfer functions from control to output and from input to output of a buck-boost converter. In order to investigate necessity of a controller for the converter with assumed parameters, the frequency and time domain analysis is done and the open loop system characteristics are verified. In addition, the needed closed loop controlled system specifications are determined. Moreover, designing a controller for the mentioned converter system based on the extracted model is discussed. For this purpose, a proportional-integral-derivative (PID) controller is designed and the hybrid of genetic algorithm (GA) and particle swarm optimization (PSO), called H-GA-PSO method is used for tuning of the PID controller. Finally, the simulation results are used to show the performance of the proposed modeling and regulation methods.